Reformulasi Islam dan Iman : Kembali kepada Tanzil Hakim dalam Perspektif Muhammad Syahrur - M. Zainal Abidin (Millah: Journal of Religious Studies, 2003)
This paper tries to elaborate the Syahrur's thought on Islam and Iman. Based on research on Tanzil Hakim, Syahrur identified that actually the pillars of Islam are the belive in Allah; the believe in the day after; and the good deed. If these three pillars can be fulfilled, someone may be called as a Muslim. The acceptance of those pillars are the begining for the people to come to the Iman, namely believe in the prophet hood of Muhammad, doing the prayer, spend the title, fasting in Ramadhan month, pilgrim to Mecca, syura (democracy) and jihad. Syahrur in formulating the pillars of Islam and Iman, put his argumentations in al Qur'an by the using the rigid linguistic analysis, but it can be understood for the mission of Syahrur is the spirit to refer to the sacred texts. The formulation of Islam is universal, while the formulation of Iman is particular.